2015
DOI: 10.1371/journal.pone.0134288
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Expression Profile of AREB/ABF and DREB/CBF Genes under Drought and Salinity Stresses in Grape (Vitis vinifera L.)

Abstract: Expression patterns of four candidate AREB/ABF genes and four DREB/CBF genes were evaluated in leaf and root tissues of five grape varieties (‘Qalati’, ‘Kaj Angoor’, ‘Sabz Angoor’, ‘Siahe Zarghan’, ‘Bidane Safid’) with differential response to drought stress. Among the AREB/ABF genes, AREB1 and ABF2 showed up-regulation in response to drought stress in leaf and root tissues of all varieties while AREB2 and ABF1 showed down-regulation in both leaf and root tissues of the sensitive variety ‘Bidane Sefid’ in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 52 publications
2
48
0
1
Order By: Relevance
“…In addition, we have observed that the gaseous treatment applied to Cardinal bunches induced the expression of other members of this transcription factor family such as CBF/DREB ( Fernandez-Caballero et al, 2012 ). The CBF/DREB proteins play a crucial role in abiotic stress-mediated gene expression, representing one of the most attractive regulons for breeding programs ( Zandkarimi et al, 2015 ) to cope with cold stress. Different studies have indeed shown the relationship between CBF/DREB expression and cold tolerance in different fruit such as tomato, peach, kiwifruit, and mango during low temperature storage in combination with different postharvest treatments ( Liang et al, 2013 ; Ma et al, 2014 ; Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have observed that the gaseous treatment applied to Cardinal bunches induced the expression of other members of this transcription factor family such as CBF/DREB ( Fernandez-Caballero et al, 2012 ). The CBF/DREB proteins play a crucial role in abiotic stress-mediated gene expression, representing one of the most attractive regulons for breeding programs ( Zandkarimi et al, 2015 ) to cope with cold stress. Different studies have indeed shown the relationship between CBF/DREB expression and cold tolerance in different fruit such as tomato, peach, kiwifruit, and mango during low temperature storage in combination with different postharvest treatments ( Liang et al, 2013 ; Ma et al, 2014 ; Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…thaliana [ 61 ]. Under saline conditions, ABF2 expression is reportedly up-regulated in grape leaves and roots in response to increasing salt concentrations [ 62 ]. Thus, the expression of salt-responsive genes may be related to the down-regulation of PP2C and up-regulation of ABF associated with ABA signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…In signal transduction of ABA, PP2C act as negative regulator, while SnPK2 acts as positive regulator (40,41). ABA is known to acts as an endogenous messenger in plants under stressed condition and the promoter regions of many ABAresponsive genes contain a conserved cis-element that is ABA-responsive element (ABRE), PyACGTGG/TC which plays major role in ABAdependent gene expression (37).…”
Section: Aba-dependent Gene Expressionmentioning
confidence: 99%